2005
DOI: 10.1016/j.jvs.2004.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Shear stress-stimulated endothelial cells induce smooth muscle cell chemotaxis via platelet-derived growth factor-BB and interleukin-1α

Abstract: One difficulty in the pharmacologic treatment of atherosclerosis or neointimal hyperplasia leading to restenosis is the multiplicity of activated pathways and thus potential treatment targets. This study demonstrates that shear stress, a hemodynamic force that may be a biologically relevant stimulus to induce vascular pathology, stimulates endothelial cells to secrete PDGF-BB and IL-1alpha. Both of these mediators stimulate the SMC ERK1/2 pathway to induce migration, a critical event in the pathogenesis of ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 63 publications
1
49
0
1
Order By: Relevance
“…This is because PDGF expression is sensitive to changes in flow, and PDGF is thought to play a major role in SMC migration during pathologic arterial remodeling [19,20]. Rat A-10 cells exposed to BMP4 exhibited less PDGF-induced migration in a dose dependent manner.…”
Section: Bmp Receptor Activation Inhibits Smc Migrationmentioning
confidence: 99%
“…This is because PDGF expression is sensitive to changes in flow, and PDGF is thought to play a major role in SMC migration during pathologic arterial remodeling [19,20]. Rat A-10 cells exposed to BMP4 exhibited less PDGF-induced migration in a dose dependent manner.…”
Section: Bmp Receptor Activation Inhibits Smc Migrationmentioning
confidence: 99%
“…Since EC actively participate in local immune and inflammatory responses, differences in endothelial immunogenicity might account for vascular bed-specific variations in susceptibility to pathological conditions. Several reports over the last years, the majority derived from human umbilical vein EC (HUVEC), have demonstrated that the local flow environment influences endothelial biosecretory and immune behavior (3,5,9,12,29,31,36,39,44).Blood flow is a complex interplay of at least three distinct mechanical forces that vary in different vascular beds: hydrostatic pressure, wall shear stress, and cyclic strains (13). The EC lining acts as an integrator and transducer of these mechanical stimuli (17) and responds with flow frequency-and shear stress-dependent modulation of nitric oxide synthase activity and prostacyclin production (4, 6).…”
mentioning
confidence: 99%
“…Since EC actively participate in local immune and inflammatory responses, differences in endothelial immunogenicity might account for vascular bed-specific variations in susceptibility to pathological conditions. Several reports over the last years, the majority derived from human umbilical vein EC (HUVEC), have demonstrated that the local flow environment influences endothelial biosecretory and immune behavior (3,5,9,12,29,31,36,39,44).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In atheromas, PDGF-BB levels may not match those found to induce migration in Fig. 1g; other factors may modify migration in vivo [2,3,27].…”
Section: Pdgf-bb and Glucose Effects On Pdgf-βr Protein Levelmentioning
confidence: 89%